An introduction to numerical analysis - Süli, Endre, 1956- (Cambridge University Press, 2003)
Based on a successful course at Oxford University, this book gives an authoritative introduction to numerical analysis. It is ideal as a text for students in the second year of a university mathematics course. It combines practicality regarding applications with consistently high standards of rigour. Numerous exercises are provided.